235 Pyjama Paralysis: Time to Make a Move!. (16th September 2019) - Fitzpatrick, Donal; Doyle, Kate; Finn, Gerard; Gallagher, Paul
Abstract: Background: The adverse effects of inpatient falls are well known. The harms of unwarranted bedrest and prolonged immobilisation present insidiously but, arguably, have a greater impact. Deconditioning, itself, is a major contributor to falls in older adults. There is still a troubling assumption that falls can be prevented through restraint and preventing at-risk patients from mobilising. Methods: We reviewed medical and nursing notes and conducted brief-structured interviews with nurses and brief bedside observations for medical inpatients aged ≥75. We constructed a research template based on the UK National Falls audit 2015 1 and the Hospital Elder Life Program (HELP) - mobility toolkit 2 . We included all patients on medical wards over the age of 75, admitted for 3 or more days. We excluded patients who were critically unwell or imminently dying. Results: We reviewed 100 medical inpatients aged over 75. Patients' mobility deteriorated significantly from their baseline, with 73% of patients requiring assistance compared to 22% at baseline. PJ paralysis was endemic with only one third of patients wearing day clothes. 75% of patients spent more than half of the day in bed. There were 8 falls during the entire study period. Poorer levels of mobility correlated with delirium and incontinence. Conclusion: The deleterious effects on older patient of the traditional model of acute hospital care with gratuitous bedrest are universally acknowledged. Falls should be prevented through supervision rather than restraint. Campaigns such as "End PJ Paralysis" and the HELP mobility toolkit can enable a cultural change within hospitals. Such change is impossible without the staffing and leadership to endorse it.